2020
DOI: 10.35678/2539-5645.1(20).2020.23-29
|View full text |Cite
|
Sign up to set email alerts
|

Smart Classroom Improvement Using Web Applications

Abstract: This paper presents the development of web applications to support smart classroom. This research describes the web application which teachers and students can use on their mobile devices such as smartphones, tablets or laptops. The core idea behind this study is that web application motivates students to study in the classroom. The population of our research is 50 Computer Engineering students. The survey shows that the ease of using the application scores 4.40. The functions of the application score 4.44. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…People also favour sharing infographics to their peers via social networks. This is in line with a study of [16,17] on the development of infographic media for an introduction to network course for 3rd year vocational students which found that learners' satisfaction towards the infographics was at the highest level [18]. The conclusion of the study "Designing of Infographic via Android Operating System Application for Royal Graduation Ceremony of Ramkhamhaeng University" is as follows;…”
Section: Resultssupporting
confidence: 82%
“…People also favour sharing infographics to their peers via social networks. This is in line with a study of [16,17] on the development of infographic media for an introduction to network course for 3rd year vocational students which found that learners' satisfaction towards the infographics was at the highest level [18]. The conclusion of the study "Designing of Infographic via Android Operating System Application for Royal Graduation Ceremony of Ramkhamhaeng University" is as follows;…”
Section: Resultssupporting
confidence: 82%